A Formação Inicial e Continuada dos Professores de Química: Uma Análise do Quadro Docente de Barreiras – Bahia - Marcelo Ribeiro dos Santos; Eduardo Luiz Dias Cavalcanti (Orbital: The Electronic Journal of Chemistry, 2016)
This paper analyzes the initial and continued formation the teaching staff of chemistry in High School of the public network of Barreiras-BA, for to know the yours main training needs. By questionnaires applied in the twelve state schools was possible to get necessary information for to trace the profile these professionals of basic education. The data analysis showed the training needs these professors and that they are related, mainly, to absence of didactic and pedagogical formation in their initial formation and also the deficiency of specific knowledge generated by an inadequate formation for the teaching function in the chemistry teaching. The results show yet that more than half these professors do not have graduation degree complete and they are not permanent teaching staff, showing the need of professionals in this area. Discussions about continued formation show that most chemistry professors do not has interest to make improvement and/or specialization for chemistry teaching, factor that favors the devaluation of the teacher in the society and shows to simple vision about chemistry teaching.DOI: http://dx.doi.org/10.17807/orbital.v1i1.710